Global, regional, and national burden of neglected tropical diseases and malaria, 1990–2021 - Talaiti Tuergan; Aimitaji Abulaiti; Alimu Tulahong; Ruiqing Zhang; Yingmei Shao; Tuerganaili Aji (Environmental Health and Preventive Medicine, 2025)
Background: Neglected tropical diseases (NTDs) and malaria pose a major health challenge, especially in low- and middle-income countries. Methods: Initially, we performed a descriptive analysis of the Global Burden of Disease (GBD) 2021 database, categorizing data by subtypes. Next, linear regression models were employed to analyze temporal trends. We then utilized four predictive models to forecast the future burden. Additionally, we explored the relationship between estimated annual percentage change (EAPCs) and age-standardized rates (ASRs), as well as Human Development Index (HDI) scores for 2021. Furthermore, decomposition analysis was applied to assess the influence of aging, population dynamics, and epidemiological changes. Lastly, frontier analysis was conducted to examine the connection between disease burden and sociodemographic development. Results: In 2021, NTDs and malaria contributed significantly to the global disease burden, with considerable disparities across genders, age groups, Socio-demographic Index (SDI) regions, GBD regions, and individual countries. From 1990 to 2021, both the number of cases and the associated ASRs have shown a recent downward trend. The EAPCs are positively correlated with ASRs and HDI scores. Projections indicate a continued decline in disease burden through 2046. Additionally, our decomposition analysis highlighted the positive impact of aging and epidemiological shifts on the reduction of the disease burden. Finally, frontier analysis revealed that countries and regions with higher SDI scores have greater potential for further reducing their health burden. Conclusion: While the global burden of NTDs and malaria has improved overall, significant disparities remain across regions and countries. Our findings highlight the importance of implementing targeted intervention strategies and maintaining sustained investments to tackle the ongoing challenges.